2022
DOI: 10.1002/bab.2346
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of the branched‐chain fatty acid biosynthesis pathway to enhance surfactin production from Bacillus subtilis

Abstract: Surfactin, which is composed of a β‐hydroxy fatty acid chain and a peptide ring, has drawn considerable attention due to its potential applications in the biomedicine, bioremediation, and petroleum industries. However, the low yield of surfactin from wild strains still restricts its industrial applications. In this study, eight genes relevant to the fatty acid biosynthesis pathway were targeted to enhance surfactin production, and high surfactin‐yielding strains with potential industrial applications were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous studies showed that lipids form complexes with amylose and LOX 2 acts on the complex formed by starch and lipids to increase the solubility of starch [ 40 ]. TraesCS2B01G535700 on chromosome 2B (731.5 Mb), TraesCS3A01G451100 on chromosome 3A (689.5 Mb) and TraesCS3D01G444000 on chromosome 3D (553.2 Mb) encode 3-ketoyl COA synthases involved in the fatty acid biosynthesis pathway [ 41 ]. Previous studies indicated that interaction between lipids and proteins has a significant impact on the rheological properties of dough.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that lipids form complexes with amylose and LOX 2 acts on the complex formed by starch and lipids to increase the solubility of starch [ 40 ]. TraesCS2B01G535700 on chromosome 2B (731.5 Mb), TraesCS3A01G451100 on chromosome 3A (689.5 Mb) and TraesCS3D01G444000 on chromosome 3D (553.2 Mb) encode 3-ketoyl COA synthases involved in the fatty acid biosynthesis pathway [ 41 ]. Previous studies indicated that interaction between lipids and proteins has a significant impact on the rheological properties of dough.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the biotin ligase coding gene birA and the biotin carboxylase II coding gene yngH , which are also involved in converting acetyl CoA to malonyl CoA, could also increase fengycin production [ 46 , 48 ]. However, although ldeHA , which encodes biotin carboxylase, has been reported to increase ACC activity and promote fatty acid biosynthesis [ 91 ], overexpression of ldeHA resulted in a significant decrease in fengycin production [ 75 ]. This may be due to the disruption of intracellular balance.…”
Section: Enhancing Fengycin Production Through Metabolic Engineeringmentioning
confidence: 99%
“…Strategies, such as increasing the pool of CoA-linked precursors by inhibiting their utilization for branched-chain fatty acid biosynthesis, overexpression of the rate-limiting enzyme in fatty acid biosynthesis to increase malonyl-ACP formation, and relieving the feedback inhibition on fatty acid synthesis by inhibiting degradation steps have all been shown to be effective. 197,208,209 However, it is important to consider the potential impact on the production prole of different surfactin variants from the same BGC, as metabolic adaptations can shi the relative production levels. 209 Similar results have been reported for fengycin biosynthesis.…”
Section: Reviewmentioning
confidence: 99%
“…197,208,209 However, it is important to consider the potential impact on the production prole of different surfactin variants from the same BGC, as metabolic adaptations can shi the relative production levels. 209 Similar results have been reported for fengycin biosynthesis. 198 In another elegant study, CRISPRi was used to investigate the inuence of amino acid metabolism on surfactin biosynthesis, allowing the identication of several genes that could be targeted for improved yields.…”
Section: Reviewmentioning
confidence: 99%